Impact of Immediacy of Feedback on Continuous Intentions to Use Online Learning From the Student Perspective - Yu, Rong; Cai, Xuerui (Frontiers in Psychology, 2022)
Advancements in Information and Communication Technology (IT) add new features into educational medium and learning environment. Enhanced interactivity on online learning environment like the immediacy of feedback is assumed to increase the interactivity of the user with online interfaces to enhance positive impact on continuous intentions to use of IS for learning. Online learning is one of these services that has become popular due to its lower cost and more accessibility. There is an immense need to assess the impacts of the immediacy of feedback on continuous intentions to use online learning to determine the acceptance of online learning by students. The study intends to explore the impacts of the immediacy of feedback on continuous intentions to use the online system from students’ perspectives by integration of the Technology Acceptance Model (TAM) and Information System Continuance Model (IS Continuance). The effect of the immediacy of feedback of media on continuous intentions to use online learning is explored directly as well as through mediation effect of student’s Perceived Ease of Use (PEU), satisfaction, attitude, Perceived Usefulness (PU) of online learning. The proposed model analyzed using Structural Equation Model (SEM). The survey data is collected from graduate and master students with at least one-semester experience of online learning. The measurement model is used to determine the validity and reliability of the model. The structural model is used to establish the hypotheses. It is observed that continuous intentions to use online learning are positively correlated with the immediacy of feedback directly as well as through the mediation effect. The immediacy of feedback in media is positively correlated with students' continuous intentions to use online line learning by the indirect effect of satisfaction, attitude, PEU, and PU. Moreover, students’ impact of problem-solving skills on continuous intentions to use online learning is improved with the immediacy of feedback.